RESPIRATION AND AMMONIA EXCRETION RATES OF THE ANTARCTIC KRILL, Euphausia superba DANA (Collected Abstracts of Transactions of the Tokyo University of Fisheries No. 5,March 1982) - SEGAWA, Susumu; KATO, Mitsuo; MURANO, Masaaki (1982)
P(論文) departmental bulletin paper